The Benefits of Mursalat Related to Early Marriage: Implementation and Orientation From an Islamic Legal Perspective - Widiyanto, Hari; Arifuddin, Qadriani; Khasanah, Fitrohtul; Fathudin; Saifudin; Muhajir (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Early marriage is a growing phenomenon in many countries, including countries with a Muslim majority. In the perspective of Islamic law, marriage is a part of worship that is highly valued, but there are provisions that must be considered so as not to harm the parties involved, especially in the context of early marriage. One approach used to assess whether early marriage is permitted or not in Islamic law is through the concept of maslahat mursalat, which is an effort to achieve public welfare that is not explicitly regulated in the Shari'a, but can be taken based on the goals and basic principles of Islam. This paper aims to analyze the application of the concept of maslahat mursalat in the context of early marriage, as well as its implications for the implementation of Islamic law. This study includes an analysis of the social, economic, and health impacts associated with early marriage, and discusses how Islamic law assesses young marriage by considering maslahat and mudarat (benefits and disadvantages). This study also seeks to examine how the orientation of maslahat mursalat can help align Islamic law with the needs of today's society, amidst the challenges of early marriage that often ignore the emotional, social, and physical readiness of individuals. The results of this study indicate that from the perspective of maslahat mursalat, early marriage is only permitted if it meets the criteria of greater welfare and does not bring harm to the parties involved. In addition, policy recommendations regarding early marriage need to consider various factors that support individual welfare, including education, mental readiness, and social and economic support. Therefore, the implementation of early marriage must be carried out carefully and wisely, ensuring that it does not violate the basic principles of Islamic law which emphasize the welfare of humanity.